2011
DOI: 10.11121/ijocta.01.2012.0050
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fleet Assignment: A Case Study in Turkey

Abstract: Since poor fleet assignment can cause a great increase in costs for airline companies, a solution of the type 'right fleet for the right flight' would be very useful. In this paper, a fleet assignment model is set up using the data of the largest Airline Company in Turkey, Turkish Airlines. The aim of this model is to assign the most appropriate fleet type to flights while minimizing the cost and determining the optimal number of aircraft grounded overnight at each airport. We set up a model with constraints w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The fleet assignment process is usually depending on the airline's flight network and it formed as a mixed integer program [18]. Two main trends were used when constructing networks: the use of arcs to represent connections (connected networks), and the use of arcs to represent flight segments (time-space networks).…”
Section: Research Methods 21 Fleet Assignment Problem Formulationmentioning
confidence: 99%
“…The fleet assignment process is usually depending on the airline's flight network and it formed as a mixed integer program [18]. Two main trends were used when constructing networks: the use of arcs to represent connections (connected networks), and the use of arcs to represent flight segments (time-space networks).…”
Section: Research Methods 21 Fleet Assignment Problem Formulationmentioning
confidence: 99%
“…Cases related to costs can be studied from a research conducted in Turkey (Ozdemir et al, 2012) that aimed to minimize the total cost while determining the number of aircrafts staying overnight at hangar. Another study, which is similar but conducted in Indonesia in a different year and objects (Blegur et al, 2014), suggested three scenarios for fleet assignment with their respective objectives, i.e.…”
Section: Previous Researchmentioning
confidence: 99%
“…Parameter 𝐵 𝑖,𝑗 indicates the cost of using fleet type j for flights I, while 𝑁 𝑗 indicates the number of attributed to the average demand (the number of passengers) which was higher than the seat capacity of Boeing 737-800NG. Meanwhile, in Ozdemir et al (2012), almost half (47.82%) of the total flights on the day were served by B737 even though the number of fleets was smaller than the other fleet types. In relation to demand, indeed 54.34% of the number of passengers was still below the B737 seat capacity.…”
mentioning
confidence: 98%
See 1 more Smart Citation